The Numerical Calculation and Laboratory Model Validation Analysis of Mechanical Noise Based on Benchmark Submarine Model. Issue 1 (June 2020) - Lv, Shuai; Yang, Xuemeng; Cao, Feng
Abstract: The mechanical noise analysis of ship structure based on finite element method has been an important means of mechanical noise assessment in the initial design stage of ships. This article is based on the Benchmark standard submarine model, carrying out the numerical simulation of the Benchmark submarine scale model, and obtaining the first-order and second-order natural vibration characteristics of the model. At the same time, we establish a laboratory test system of the Benchmark submarine scale model, and test the natural vibration characteristics of the model under laboratory conditions. We compare numerical simulations and experimental laboratory test results, optimize the numerical modeling method and find the reliability of the numerical simulation calculation. Based on the above research, modeling a true-scale Benchmark standard submarine model, calculate the natural vibration characteristics of the Benchmark submarine model in the ocean flow field environment. Then calculate the value of mechanical radiation noise under the excitation of mechanical equipment based on the natural vibration characteristics results.